Augmented books - Lazić, Nikolaj (2011)
When dealing with students and their reading habits, differences regarding their media preferences can still be observed: some love books and some love multimedia in any form. There is always a struggle when the teacher tries to enforce only one medium. Augmented book could be the answer to reconciliation between two opposed sides. 2D matrix barcode is a technology that could provide expansion to the book directing students seeking “cool media” to the Internet for additional multimedia and possibly gradually immerse reluctant students into using all the benefits of e-learning environments and the Internet. At the same time, the opposite group is invited to read the augmented printed book. Augmented book does not need additional physical media to hold sounds, photograpgs or movies This paper shows the theoretical background and practical benefits of publishing books augmented with 2D matrix barcode.